SISTEM REKOMENDASI PEMILIHAN DESTINASI WISATA DI MALANG MENGGUNAKAN METODE TOPSIS - rully fajar alfitroni; Umi Chotijah; Putri Aisyiyah Rakhma Devi (Indexia : Informatics and Computational Intelligent Journal, 2021)
Along with the development of science from time to time, technology and information also develop rapidly. The sophistication of information technology that is currently developing is not only useful for intelligence purposes, but has penetrated into the world of industry and tourism as well CV. TRAVELINDO ADVENTURE is a company engaged in travel agency. In choosing the best tourist destinations that will be included in the service package, CV. TRAVELINDO ADVENTURE is currently still random and only based on information obtained manually. Based on above description, the problem that often occurs is the inaccuracy in choosing the best tourist destinations. According to the delivery from the manager to all employees, the determination of tourist destinations must be based on criteria that have been determined by the company. In this process, the ratings are displayed in a table and sorted from the highest to the lowest score. Several Decision Support System methods that can help the problems above have been tested, and one method is chosen from several methods that have been tested. The method is Technique For Others Reference by Similarity to Ideal Solution, or commonly called TOPSIS